Myocardial Perfusion Is Impaired and Relates to Cardiac Dysfunction in Patients With Atrial Fibrillation Both Before and After Successful Catheter Ablation. Issue 15 (7th August 2018) - Wijesurendra, Rohan S.; Liu, Alexander; Notaristefano, Francesco; Ntusi, Ntobeko A. B.; Karamitsos, Theodoros D.; Bashir, Yaver; Ginks, Matthew; Rajappan, Kim; Betts, Tim R.; Jerosch‐Herold, Michael; Ferreira, Vanessa M.; Neubauer, Stefan; et al.
Abstract : Background: Atrial fibrillation (AF) is associated with myocardial infarction, and patients with AF and no obstructive coronary artery disease can present with symptoms and evidence of cardiac ischemia. We hypothesized that microvascular coronary dysfunction underlies these observations. Methods and Results: Myocardial blood flow (MBF) at baseline and during adenosine stress and left ventricular and left atrial function were evaluated by magnetic resonance in 49 patients with AF (25 paroxysmal, 24 persistent) with no history of epicardial coronary artery disease or diabetes mellitus, before and 6 to 9 months after ablation. Findings were compared with those obtained in matched controls in sinus rhythm (n=25). Before ablation, patients with AF had impaired left atrial function and left ventricular ejection fraction and strain indices (all P <0.05 versus controls). MBF was impaired in patients both under baseline conditions (1.21±0.24 mL/min per g·[mm Hg·bpm/10 4 ] −1 versus 1.34±0.28 mL/min per g·[mm Hg·bpm/10 4 ] −1 in controls, P =0.044) and during adenosine stress (2.29±0.48 mL/min per g versus 2.73±0.37 mL/min per g in controls, P <0.001). Under baseline conditions, MBF correlated with left ventricular strain and left atrial function (all P ≤0.001), so that cardiac function was most impaired in patients with the lowest MBF. Baseline and stress MBF remained unchanged postablation (both P =ns), and baseline MBF showed similar correlations with functional indices to those present preablation (all P ≤0.001). Conclusions: Baseline and stress MBF are significantly impaired in patients with AF but no epicardial coronary artery disease. Reduction in MBF is proportional to severity of left ventricular and left atrial dysfunction, even after successful ablation. Coronary microvascular dysfunction may be a relevant pathophysiological mechanism in patients with a history of AF.